Exploring The Factors Influencing Anxiety in ESL Teaching Interns Across Different Education Levels - Galuhwardani, Cindyra (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Kadiri, 2024)
This study examines the anxiety experienced by ESL teacher-interns in Indonesia, specifically those teaching English in primary and secondary schools, and how this anxiety impacts their teaching. As they are still in the process of learning to teach, many teacher-interns feel nervous using English in the classroom. This anxiety can hinder their ability to deliver lessons effectively and engage students. Using a qualitative research approach, the study collected data through interviews with four teacher-interns from different school levels. The findings reveal that anxiety stems from four key factors: lesson preparation, classroom conditions, lack of confidence, and physical health. Many teacher-interns struggle with managing students, planning lessons, and maintaining confidence in their English skills. Large class sizes and student behavior further contribute to their stress. Additionally, some interns fear making mistakes, and teaching becomes even more challenging when they are tired or unwell. The study underscores the importance of improved training, mentorship, and emotional support to help teacher-interns build confidence and enhance their teaching effectiveness.